Penerapan 7P sebagai Strategi Pemasaran Pendidikan Tinggi Islam - Neneng Hasanah (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Competition between job seekers is very high, this is evidenced by the high unemployment rate recorded by the Central Statistics Agency (BPS) recently which released Indonesia's labor conditions as of February 2019. Data shows the unemployment rate fell to 5.01 percent or decreased by 50 thousand people over the past year. The Open Unemployment Rate (TPT) as of February 2019 was 6.82 million people. Judging from the declining unemployment rate, but when viewed from the level of education of diploma and university graduates more and more are not working. The researcher uses a qualitative-naturalistic approach with the aim of knowing the projections of promotion of Islamic higher education through 7P. Through this qualitative approach, it is hoped that a picture of the quality, social reality and perceptions of the research target will be raised without being polluted by formal measurements. The naturalistic approach demands data collection in a natural setting. With this concept, the researcher strives for the presence of the researcher not to change the situation or behavior of the person being studied.